Fungal diversity rather than bacterial diversity drives the ecosystem multifunctionality of vineyards in a semi-arid region - Duan, Bingbing; Ren, Yizhao; Zhang, Leqi; Suzhou, Chenxing; Chen, Guoqiao; Cui, Ping; Zhangyang, Yusong; Liu, Wei; Merkeryan, Hasmik; Liu, Xu (International Journal of Agricultural and Biological Engineering, 2021)
The presence of multiple ecosystem functions and services (i.e., ecosystem multifunctionality) has been proven to be maintained by biodiversity in natural terrestrial ecosystems. However, the mechanisms by which microbial diversity drives ecosystem functions in vineyards and the effects of ecosystem functions on wine quality remain unknown. Here, fifteen vineyards from five wine sub-regions (Shizuishan, Yinchuan, Yuquanying, Qingtongxia, and Hongsipu) in Ningxia were selected to assess the microbial community structure, ecosystem multifunctionality, and wine quality. Overall, each index differed among the vineyards from these five wine sub-regions in Ningxia. High-throughput sequencing revealed that bacterial and fungal communities varied among these vineyards. Bacterial communities were dominated by Actinobacteria, Proteobacteria, Chloroflexi, and Acidobacteria. Ascomycota was the dominant fungal phylum, followed by Basidiomycota and Mortierellomycota. In addition, fungal Shannon diversity rather than bacterial Shannon diversity showed a positive relationship with ecosystem multifunctionality. Correlation analysis revealed that ecosystem multifunctionality was positively correlated with wine acidity and negatively correlated with pH value and residual sugar content of wine. Soil chemical functions exhibited relationships with wine quality being similar to those of ecosystem multifunctionality; i.e., positively related to wine acidity but negatively related to wine pH and residual sugar content. However, soil physical functions were negatively correlated with the alcohol and anthocyanin content of wine. The research results show that the ecosystem functions maintained by fungal diversity could be attributed to wine quality of vineyards. Keywords: microbial diversity, multifunctionality, terroir, wine quality, wine sub-regions DOI: 10.25165/j.ijabe.20211406.5560 Citation: Duan B B, Ren Y Z, Zhang L Q, Suzhou C X, Chen G Q, Cui P, et al. Fungal diversity rather than bacterial diversity drives the ecosystem multifunctionality of vineyards in a semi-arid region. Int J Agric & Biol Eng, 2021; 14(6): 126–136.